Isothermal relaxation kinetics for the reduction and oxidation of SrFeO3 based perovskites. Issue 4 (15th January 2020) - Bulfin, B.; Vieten, J.; Richter, S.; Naik, J. M.; Patzke, G. R.; Roeb, M.; Sattler, C.; Steinfeld, A.
Abstract : The perovskite oxide SrFeO3 has favourable redox properties for oxygen exchange applications, including oxygen separation and oxygen production chemical looping cycles. Abstract : The perovskite oxide SrFeO3 has favourable redox properties for oxygen exchange applications, including oxygen separation and oxygen production chemical looping cycles. For such applications, lower temperature operation can improve the energy demand and feasibility of the process, but can also lead to kinetic limitations. Here we investigate the oxidation and reduction reaction kinetics of SrFeO3 in the temperature range 450–750 K. Isothermal relaxation techniques are used to observe the reaction rates across this temperature range, using a thermogravimetric analysis system. Experimental data are analysed according to an isoconversional method and fit with a simple power law model to extract activation energies. The apparent activation energy of oxidation and reduction was found to be 92 ± 16 and 144 ± 17 kJ mol −1 respectively. Comparison of oxidation and reduction kinetics together with considerations of particle size indicate that the oxidation reaction rate may be limited by diffusion in the bulk, while the reduction reaction rate is limited by the surface reaction. Furthermore, we also investigated the mixed perovskite Sr0.93 Ca0.07 Fe0.9 Co0.1 O3, which exhibited a 4-fold increase in the oxidation rate.